PERBAIKAN SISTEM PENGEREMAN PADA MESIN BUBUT DoAll Lt 13 DI BENGKEL MEKANIK POLMAN BABEL - Ferdian, Ferdian; Ariansyah, Ariansyah; Napitupulu, Robert; Pristiansyah, Pristiansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Repair the braking system on the DoAll Lt 13 no 4 lathe In completing the final project entitled Repair of the Cooling System and Braking System on the Doall Lt13 Lathe at the Bangka Belitung State Manufacturing Polytechnic, stages of adjustment are made to the flowchart diagram. Problem identification is a crucial stage because if the problem is not identified correctly, the solution applied may not be effective or may even worsen the situation, accurate and in-depth identification also helps ensure that the solution developed will be relevant and effective. In the data collection action there are several methods used to find out the problems and damage that occur in the DoAll LT 13 lathe. The methods used are the technician interview method, looking at the manual book, looking at the machine history book and conducting direct observation on the machine. The following is the initial data from several methods carried out Based on the results of the DoAll LT13 Lathe Brake System repair function test using a clutch motor braking system, the braking system was successfully repaired, and was able to work well and was able to brake. And for the repair of the cooling system on the DoAll Lt 13 no 4 lathe, it was also successfully repaired and obtained optimal results for all components that were repaired.